Complex masking agent for inhibiting impurity co-solubility and its use in leaching of platinum group metals from spent catalysts

CN122428135BActive Publication Date: 2026-10-20JIANGXI CHANGCHI NEW MATERIAL TECHNOLOGY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610645545.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-12
Publication Date
2026-10-20
Estimated Expiration
2046-05-12

AI Technical Summary

Technical Problem

[0003]然而,该体系面临长期未解决的共性难题:(1)载体 γAl2O3与 Fe、Ni、Cu、Zn 等贱金属大量共溶;(2)杂质离子大幅增加酸耗、氧化剂消耗与后续分离成本;(3)杂质水解生成胶体,降低铂族金属浸出率与过滤性能

Benefits of technology

1.本发明采用酒石酸钾钠、硫代硫酸钠、乙二胺四乙酸二钠、表面钝化剂和多酚类黏附剂五组分协同体系,实现了对废催化剂中铝、铁、镍、铜、锌等多种贱金属杂质的广谱高效抑制,克服了单一掩蔽剂掩蔽谱窄、选择性差、酸性条件下易失效等缺陷,同时保障了铂族金属的高效浸出。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The application provides a composite masking agent for inhibiting impurity co-dissolution and application thereof in waste catalyst platinum group metal leaching. The composite masking agent is a three-dimensional network compound formed by compounding an oxidized cross-linked polyphenol network and a functional complex component; the functional complex component comprises potassium sodium tartrate, sodium thiosulfate, ethylenediaminetetraacetic acid disodium, and a surface passivation agent; the surface passivation agent adopts at least one of citric acid, phytic acid, gluconic acid, and tartaric acid; the oxidized cross-linked polyphenol network is obtained by oxidizing cross-linking of a polyphenol adhesive, and the polyphenol adhesive is selected from at least one of tannic acid, lignin, and a lignin derivative. The composite masking agent is used for inhibiting the dissolution of base metal impurities in the waste catalyst platinum group metal leaching process. The application realizes broad-spectrum and efficient inhibition of various base metal impurities such as aluminum, iron, nickel, copper, and zinc in the waste catalyst, overcomes defects such as narrow masking spectrum, poor selectivity, and easy failure under acidic conditions of a single masking agent, and at the same time guarantees efficient leaching of platinum group metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal solid waste resource utilization technology, and specifically relates to a composite masking agent for inhibiting the co-solubility of impurities and its application in the leaching of platinum group metals from waste catalysts. Background Technology

[0002] Platinum group metals (Pt, Pd, Rh) are strategically scarce resources, and spent catalysts (automotive exhaust catalysts, petrochemical reforming catalysts, etc.) are important secondary resources of platinum group metals. Mainstream hydrometallurgical processes employ a hydrochloric acid + oxidant (chlorine, sodium chlorate, hydrogen peroxide, etc.) system to form [PtCl6]. ]2- [PdCl4] 2- Isochlorination complexes enable efficient leaching of PGMs.

[0003] However, this system faces a common problem that has remained unsolved for a long time: (1) the carrier γ Al2O3 co-dissolves extensively with base metals such as Fe, Ni, Cu, and Zn; (2) impurity ions significantly increase acid consumption, oxidant consumption, and subsequent separation costs; (3) impurities hydrolyze to form colloids, reducing the leaching rate of platinum group metals and filtration performance. Expired catalyst supports (γ-Al2O3, etc.) and the base metals they contain (Fe, Cu, Ni, Zn, Ce, La, etc.) dissolve extensively into the leachate under strong acid and strong oxidizing conditions, leading to increased chemical consumption, difficulty in impurity separation, and reduced leaching rate of precious metals. Existing technologies mostly use single complexing agents or simple compound masking agents, which generally suffer from narrow masking spectrum, poor selectivity, easy failure under strong acid oxidizing conditions, and inability to balance high leaching rate and high impurity suppression rate, making them difficult to apply industrially. Summary of the Invention

[0004] In view of this, the present invention provides a composite masking agent for inhibiting the co-solubility of impurities and its application in the leaching of platinum group metals from spent catalysts, aiming to solve at least one technical problem in the prior art.

[0005] This invention is implemented as follows: The first aspect of the present invention provides a composite masking agent for inhibiting the co-solubility of impurities, wherein the composite masking agent is a three-dimensional network complex formed by combining an oxidized cross-linked polyphenol network with a functional complexing component; The functional complexing components include sodium potassium tartrate, sodium thiosulfate, disodium ethylenediaminetetraacetate, and a surface passivating agent; the surface passivating agent is at least one selected from citric acid, phytic acid, gluconic acid, and tartaric acid. The oxidatively cross-linked polyphenol network is obtained by oxidatively cross-linking a polyphenolic adhesive, wherein the polyphenolic adhesive is selected from at least one of tannic acid, lignin, and lignin derivatives.

[0006] Furthermore, the composite masking agent comprises the following components in parts by weight: 8 to 20 parts of potassium sodium tartrate; Sodium thiosulfate 15 to 30 parts; 5 to 15 parts of disodium ethylenediaminetetraacetate; 15 to 35 parts of surface passivating agent; 5 to 20 parts of polyphenolic adhesive.

[0007] Furthermore, the preparation method of the composite masking agent includes the following steps: S11. Dissolve the polyphenolic adhesive and adjust the pH to 7.0~10.0, add the oxidant, and react at 40℃~70℃ for 0.5h~6h to form an oxidative crosslinking product; S12. Dissolve potassium sodium tartrate, sodium thiosulfate, disodium ethylenediaminetetraacetate, and a surface passivating agent, and then combine them with the oxidative crosslinking compound to obtain a liquid composite masking agent; or obtain a solid composite masking agent by spray drying.

[0008] Furthermore, the oxidant is hydrogen peroxide, and its addition amount is 0.5% to 2.0% of the mass of the polyphenolic adhesive.

[0009] Furthermore, the conditions for compounding are as follows: pH adjusted to 4.0~5.5, and stirred for 30min~90min at a temperature of 40℃~60℃.

[0010] Furthermore, the lignin derivative is sulfonated lignin, carboxymethylated lignin, aminated lignin, or oxidized ammonolytic lignin.

[0011] A second aspect of the present invention provides the application of a composite masking agent for inhibiting the co-dissolution of impurities in the leaching of platinum group metals from spent catalysts. The composite masking agent is used to inhibit the co-dissolution of base metal impurities during the leaching of platinum group metals from spent catalysts. The base metal impurities include at least one of aluminum, iron, nickel, copper, and zinc.

[0012] Furthermore, a composite masking agent is added to the waste catalyst after decarbonization pretreatment, and the catalyst is treated for 30 to 90 minutes at a pH of 4.0 to 5.5 and a temperature of 50°C to 70°C. This allows the composite masking agent to form a three-dimensional network structure in situ on the surface of the waste catalyst support before acidic oxidation leaching of platinum group metals is carried out.

[0013] Furthermore, the amount of the composite masking agent added is 4% to 10% of the dry mass of the spent catalyst.

[0014] Furthermore, the method of application specifically includes: Decarbonization pretreatment of spent catalysts; The decarbonized pretreated waste catalyst is added to the reactor, water or dilute hydrochloric acid is added to adjust the slurry, and the liquid-solid ratio is controlled at 3~5:1; then a composite masking agent is added, the pH is adjusted to 4.0~5.5, the temperature is 50℃~70℃, and the pretreatment is stirred for 30min~90min. Add hydrochloric acid-sulfuric acid mixture to lower the pH of the system to 2-3, slowly add sodium chlorate as oxidant, and raise the temperature to 85℃-105℃; continue stirring for 2-4 hours to allow the platinum group metals to enter the solution in the form of chloride complexes; after leaching is completed, filter under pressure to obtain a leachate with low impurity content.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention employs a five-component synergistic system of potassium sodium tartrate, sodium thiosulfate, disodium ethylenediaminetetraacetate, surface passivating agent, and polyphenolic binder to achieve broad-spectrum and efficient suppression of various base metal impurities such as aluminum, iron, nickel, copper, and zinc in waste catalysts. This overcomes the shortcomings of single masking agents, such as narrow masking spectrum, poor selectivity, and easy failure under acidic conditions, while ensuring efficient leaching of platinum group metals.

[0016] 2. This invention forms a stable surface chelate with the metal ions on the carrier surface through a surface passivating agent, blocking active dissolution sites and inhibiting carrier dissolution from the source. This achieves solid-phase source inhibition rather than end-of-solution removal, fundamentally reducing the risk of impurities entering the leachate.

[0017] 3. This invention utilizes the catechol groups of polyphenolic adhesives to bond with the Al groups on the carrier surface. 3+ Multi-point coordination forms a three-dimensional network structure, weaving various functional components onto the carrier surface, which enhances the stability and self-healing ability of the coating and extends the effective protection time of the masking layer.

[0018] 4. This invention uses oxidative coupling to pre-crosslink polyphenolic adhesives to form a three-dimensional network structure connected by C-C bonds or CO bonds. It does not require the addition of expensive and unstable crosslinking agents such as EDC / NHS. The preparation process is simple, low-cost, and environmentally friendly. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0020] A composite masking agent for inhibiting the co-solubility of impurities is a three-dimensional network complex formed by combining an oxidized cross-linked polyphenol network with a functional complexing component; the functional complexing component includes sodium potassium tartrate, sodium thiosulfate, disodium ethylenediaminetetraacetate, and a surface passivating agent; the surface passivating agent is at least one of citric acid, phytic acid, gluconic acid, and tartaric acid; the oxidized cross-linked polyphenol network is obtained by oxidative cross-linking of a polyphenolic adhesive, and the polyphenolic adhesive is selected from at least one of tannic acid, lignin, and lignin derivatives.

[0021] The composite masking agent for inhibiting the co-solubility of impurities comprises the following components in parts by weight: 8-20 parts potassium sodium tartrate; 15-30 parts sodium thiosulfate; 5-15 parts disodium ethylenediaminetetraacetate; 15-35 parts surface passivating agent; and 5-20 parts polyphenolic adhesive. The components of the composite masking agent are prepared by oxidative coupling to form a composite with a three-dimensional network structure. In the following examples, 12 parts potassium sodium tartrate, 18 parts sodium thiosulfate, 8 parts disodium ethylenediaminetetraacetate, 20 parts surface passivating agent, and 10 parts polyphenolic adhesive are used as examples, but the values ​​are not limited to those listed; other unlisted values ​​within the range are also applicable. The oxidative coupling method involves subjecting the polyphenolic adhesive to an oxidative cross-linking reaction under oxidative conditions to form an oxidatively cross-linked polyphenol network with a three-dimensional network structure, which is then compounded with potassium sodium tartrate, sodium thiosulfate, disodium ethylenediaminetetraacetate, and the surface passivating agent.

[0022] Sodium potassium tartrate acts as an oxidation shielding agent. In the initial leaching stage after the oxidant is added, the weak reducing property of tartrate preferentially consumes the free oxidant, establishing a reducing microenvironment on the support surface and forming a dynamic redox buffer layer, thus inhibiting the oxidative dissolution of the support (γ-Al2O3). However, when used alone, sodium potassium tartrate has a narrow masking spectrum, mainly affecting Ca2+. 2+ Mg 2+ Equally effective for Fe 3+ Cu 2+ Ni 2+ Base metals have no concealment capabilities.

[0023] Sodium thiosulfate is a competitive complexing agent; during the middle stage of leaching, it reacts with Cu. 2+ Ni 2+ Zn 2+ Base metals preferentially form stable complexes, inhibiting their hydrolysis and precipitation, and preventing colloid formation. However, sodium thiosulfate, when used alone, has a negative effect on Al... 3+ Fe 3+ They have virtually no masking ability, are unstable and easily decomposed in strongly acidic environments, and are rapidly oxidized and lose their complexing ability in the presence of strong oxidants.

[0024] Disodium ethylenediaminetetraacetate is a broad-spectrum complexing agent; during the mid-stage of leaching, it has a significant effect on Fe. 3+ Zn2+ Multivalent metal ions are broadly complexed and captured to prevent them from entering the solution phase. However, when used alone, disodium ethylenediaminetetraacetate can form stable chelates with almost all metal ions, leading to the complexation of target platinum group metal ions and reducing the leaching rate.

[0025] The surface passivating agent is at least one selected from citric acid, phytic acid, gluconic acid, and tartaric acid, preferably citric acid or phytic acid; in the later stage of leaching, the surface passivating agent reacts with the Al exposed on the carrier surface. 3+ The formation of stable five-membered ring chelates blocks active dissolution sites and creates a dense surface passivation layer, inhibiting Al2O3 production at its source. 3+ Dissolution. However, under strongly acidic conditions with pH=2~3, the carboxyl group of citric acid is protonated, and its complexing ability in the solution phase is greatly reduced.

[0026] Studies have found that simple physical mixing of potassium sodium tartrate, sodium thiosulfate, disodium ethylenediaminetetraacetate, and citric acid results in defects such as functional fragmentation of each component, easy loss of small molecules, and lack of self-repairing ability. This invention adds a polyphenolic adhesive, connecting the components into a three-dimensional network structure through chemical bonds or coordination bonds. It utilizes temporal control and functional complementarity to synergistically compensate for each component's defects, achieving molecular-level synergy, inhibiting polyphenol self-aggregation, constructing a dense physical barrier, weaving and locking impurity ions, and endowing self-repairing ability, thus achieving triple protection of solution phase masking + solid phase passivation + interface anchoring. The polyphenolic adhesive uses at least one of tannic acid, lignin, and lignin derivatives. The lignin derivatives are sulfonated lignin, carboxymethylated lignin, aminated lignin, or oxidized ammonolytic lignin; tannic acid, sulfonated lignin, and oxidized ammonolytic lignin are preferred, as tannic acid and sulfonated lignin are low-cost and commonly used products in industry. The polyphenolic adhesive binds to the Al2O3 surface of the carrier through polyphenolic groups. 3+ Multi-point coordination forms a three-dimensional network structure, weaving small molecules such as disodium ethylenediaminetetraacetate and surface passivating agents into the three-dimensional network to enhance the stability and self-healing ability of the coating.

[0027] Sulfonated lignin, carboxymethylated lignin, aminated lignin, or oxidative ammonolytic lignin can be commercially available or synthesized using existing methods; no specific limitations are specified here. The specific synthesis steps for sulfonated lignin are as follows: using industrial lignin as raw material, dissolve it in a mixture of organic solvent (such as ethanol) and water; add alkali to adjust the pH to 9-14 to activate the reaction sites; slowly add sulfonating agents such as alkyl sulfonate lactones or sodium sulfite at room temperature to 100℃, reacting for 10-24 hours; after the reaction, cool, concentrate, and purify to obtain sulfonated lignin. The specific synthesis steps for carboxymethylated lignin are as follows: dissolve lignin in 85%-95% aqueous ethanol, add sodium hydroxide solution, and alkalize at 20℃-30℃ for 1 hour; add chloroacetic acid as an etherifying agent, reacting at 50℃-80℃ for 2 hours; after the reaction, neutralize with hydrochloric acid, centrifuge to separate the precipitate, dry and pulverize to obtain carboxymethylated lignin. The specific synthetic steps for amination lignin are as follows: lignin is mixed with an amination agent (such as lysine or polyamine) and an aldehyde (such as glyoxal), and a Mannich reaction is carried out under appropriate conditions to graft amino groups onto the ortho-position of the phenolic hydroxyl groups in the lignin. After the reaction, the product is separated, purified, and dried to obtain the amination lignin product. The specific synthetic steps for oxidative ammonolytic lignin are as follows: lignin is mixed with urea peroxide (UHP), where UHP serves as both a nitrogen source and an oxidant, requiring no external solvent. The reaction is carried out in a closed reactor under heating, and the nitrogen content of the product is controlled by adjusting the ratio of UHP to lignin. After the reaction, the product is cooled, separated, and dried to obtain oxidative ammonolytic lignin.

[0028] The preparation method of this composite masking agent includes steps S11 to S12: S11. After dissolving polyphenolic adhesives in a solvent (water or 50% ethanol aqueous solution) and adjusting the pH to 7.0~10.0 (preferably 8~9), add an oxidant and react at 40℃~70℃ for 0.5h~6h to form an oxidative crosslinking product. The oxidant is hydrogen peroxide, and its addition amount is 0.5% to 2.0% of the mass of the polyphenolic adhesive. A C-bond network is formed by the spontaneous coupling of polyphenol groups in tannic acid / lignin / lignin derivatives under oxidative conditions. In specific implementations, oxygen or other oxygen can also be used as the oxidant, but it is difficult to control, therefore hydrogen peroxide is preferred.

[0029] S12. Dissolve potassium sodium tartrate, sodium thiosulfate, disodium ethylenediaminetetraacetate, and a surface passivating agent, and then combine them with the oxidative crosslinking compound to form a three-dimensional supramolecular network, thereby obtaining a liquid composite masking agent; or obtain a solid composite masking agent by spray drying.

[0030] The solvent used for dissolution can be adjusted according to actual needs. In the following examples, deionized water is used as the solvent for dissolution. Heating or adding acid can be used to adjust the dissolution process to promote dissolution.

[0031] The conditions for compounding are: pH adjusted to 4.0~5.5, and stirring at 40℃~60℃ for 30min~90min.

[0032] The composite masking agent prepared by this invention is used to suppress the leaching of base metal impurities during the platinum group metal leaching process of spent catalysts. Specifically, the composite masking agent is added to the spent catalyst after decarbonization pretreatment, and the catalyst is treated at a pH of 4.0~5.5 and a temperature of 50℃~70℃ for 30min~90min. This allows the composite masking agent to form a three-dimensional network structure in situ on the surface of the spent catalyst support before acidic oxidative leaching of platinum group metals is carried out.

[0033] The specific steps are as follows: Step 1: Decarbonization pretreatment of waste catalyst. Any decarbonization pretreatment step permitted in this field can be adopted. The purpose is as follows: the decarbonization pretreatment in the following embodiment is to crush the waste catalyst and heat it to 600°C for aerobic calcination for about 3 hours. However, it is not limited to this and other pretreatment processes are also applicable.

[0034] Step 2: Add the decarbonized pretreated waste catalyst to the reactor, add water or dilute hydrochloric acid to adjust the slurry, and control the liquid-solid ratio to 3~5:1; then add a composite masking agent, the amount of which is 4%~10% of the dry basis mass of the decarbonized pretreated waste catalyst, adjust the pH to 4.0~5.5, the temperature to 50℃~70℃, and stir for 30min~90min for pretreatment.

[0035] Step 3: Add hydrochloric acid-sulfuric acid mixture to lower the pH of the system to 2-3, slowly add sodium chlorate as oxidant, and raise the temperature to 85℃-105℃; continue stirring for 2-4 hours to allow the platinum group metals to enter the solution in the form of chloride complexes; after leaching is completed, filter under pressure to obtain a leachate with low impurity content, i.e., precious solution.

[0036] The following examples illustrate the use of solid composite masking agents.

[0037] Example 1 This embodiment describes the preparation of a composite masking agent for suppressing the co-solubility of impurities via oxidative coupling. The specific steps are as follows: S1. Weigh the following components according to their weight: 12 parts potassium sodium tartrate, 18 parts sodium thiosulfate, 8 parts disodium ethylenediaminetetraacetate, 20 parts surface passivating agent (citric acid), and 10 parts polyphenolic adhesive (sulfonated lignin). S2. Dissolve sulfonated lignin in deionized water, adjust the pH to 8 with alkali, add hydrogen peroxide (1 wt% of sulfonated lignin) as an oxidant, and react at 50°C for 3 hours to form an oxidative crosslinking product. S3. Dissolve sodium potassium tartrate, sodium thiosulfate, disodium ethylenediaminetetraacetate, and citric acid in deionized water, then add the oxidative crosslinking agent, adjust the pH to 5.0 and the temperature to 60℃, and stir the reaction for 1 hour; after the reaction is completed, cool to room temperature and spray dry to obtain a solid composite masking agent.

[0038] The composite masking agent prepared in this embodiment is used to suppress the leaching of base metal impurities during the leaching of platinum group metals from spent catalysts.

[0039] The metal content in the waste catalyst is as follows: platinum = 759.6 g / t, palladium = 320.1 g / t, rhodium = 66.7 g / t; aluminum = 352.44 kg / t, iron = 14.77 kg / t, nickel = 2.51 kg / t, copper = 1.04 kg / t, and zinc = 0.84 kg / t.

[0040] The application method steps are as follows: S4. Crush the waste catalyst and calcine it at 600℃ for about 3 hours. Add the decarbonized pretreated waste catalyst to the reactor and add water to adjust the slurry (liquid-solid ratio = 4:1); then add a composite masking agent, the amount of which is 5% of the dry basis mass of the decarbonized pretreated waste catalyst. Adjust the pH to 5, the temperature to 60℃, and stir for 60 minutes for pretreatment. Add a mixture of hydrochloric acid (4mol / L) and sulfuric acid (6mol / L) to lower the pH of the system to 2.5, slowly add the oxidant sodium chlorate (0.3mol / L), and raise the temperature to 80℃; continue stirring for 2 hours to allow the platinum group metals to enter the solution in the form of chloride complexes; after leaching, filter under pressure to obtain a leachate with low impurity content.

[0041] S4 without composite masking agent was used as a blank control group. The procedure was as follows: the spent catalyst was crushed and calcined at 600℃ for about 3 hours. The spent catalyst after decarbonization pretreatment was added to the reactor, and water was added to adjust the slurry (liquid-solid ratio = 4:1). A mixture of hydrochloric acid (4 mol / L) and sulfuric acid (6 mol / L) was added to lower the pH of the system to 2.5. The oxidant sodium chlorate (0.3 mol / L) was slowly added, and the temperature was raised to 90℃. Stirring was continued for 2.5 hours to allow the platinum group metals to enter the solution in the form of chloride complexes. After leaching was completed, the solution was filtered to obtain the leachate.

[0042] The contents of platinum group metals (platinum, palladium, and rhodium) and metallic impurities (represented by aluminum, iron, nickel, copper, and zinc) in the precious liquor were determined by inductively coupled plasma atomic emission spectrometry (ICP-AES). The leaching rate of platinum group metals and the impurity inhibition rate were calculated. Three parallel samples were set up, and the results are shown in Table 1 below.

[0043] The leaching rate of platinum group metals (%) = (C*V) / (m*ω)×100%, where C is the concentration of platinum group metals in the leachate, V is the total volume of the leachate, m is the mass of the spent catalyst, and ω is the grade of platinum group metals in the spent catalyst. Impurity inhibition rate (%) = [(C0*V0)-(C1*V1)] / (C0*V0)×100%, where C0 and V0 are the corresponding impurity concentrations and volumes in the leachate obtained from the blank control group without masking agent, respectively; and C1 and V1 are the corresponding impurity concentrations and volumes in the leachate obtained by adding composite masking agent in this embodiment, respectively.

[0044] Table 1

[0045] Example 2 Based on Example 1, this embodiment changes the type of surface passivating agent in S1 to phytic acid, while keeping other conditions the same as in Example 1. The leaching rate and impurity inhibition rate of the platinum group metals in this embodiment are tested using the same method as in Example 1, and the results are shown in Table 2.

[0046] Example 3 Based on Example 1, this embodiment changes the type of surface passivating agent in S1 to gluconic acid, while keeping other conditions the same as in Example 1. The leaching rate and impurity inhibition rate of the platinum group metals in this embodiment are tested using the same method as in Example 1, and the results are shown in Table 2.

[0047] Example 4 Based on Example 1, this embodiment changes the type of surface passivating agent in S1 to tartaric acid, while keeping other conditions the same as in Example 1. The leaching rate and impurity inhibition rate of the platinum group metals in this embodiment are tested using the same method as in Example 1, and the results are shown in Table 2.

[0048] Table 2

[0049] Table 2 shows the comparison of the effects of surface passivating agents on promoting the leaching of platinum group metals and inhibiting impurities: phytic acid ≥ citric acid > tartaric acid > gluconic acid. This is because phytic acid contains six phosphate groups, which interact with Al... 3+ Phytic acid exhibits extremely strong coordination ability, resulting in a denser passivation film. Its impurity inhibition rate is slightly higher than that of citric acid, and its platinum group metal leaching rate is also slightly improved (phytic acid has less interference with the complexation of PGMs). Citric acid offers the best cost-performance ratio: it has good overall performance, readily available raw materials, and moderate cost, making it the preferred surface passivating agent for industrial applications. Tartaric acid is less effective than citric acid, and gluconic acid is less effective; when used alone, it has the lowest impurity inhibition rate.

[0050] Example 5 Based on Example 1, this embodiment changes the type of polyphenolic adhesive in S1 to tannic acid. Other conditions are the same as in Example 1. The leaching rate and impurity inhibition rate of platinum group metals in this embodiment are tested using the same method as in Example 1. The results are shown in Table 3.

[0051] Example 6 Based on Example 1, this embodiment changes the type of polyphenolic adhesive in S1 to lignin, while keeping other conditions the same as in Example 1. The leaching rate of platinum group metals and the impurity inhibition rate of this embodiment are tested using the same method as in Example 1, and the results are shown in Table 3.

[0052] Example 7 Based on Example 1, this embodiment changes the type of polyphenolic adhesive in S1 to carboxymethylated lignin. Other conditions are the same as in Example 1. The leaching rate and impurity inhibition rate of platinum group metals in this embodiment are tested using the same method as in Example 1. The results are shown in Table 3.

[0053] Example 8 Based on Example 1, this embodiment changes the type of polyphenolic adhesive in S1 to aminated lignin. Other conditions are the same as in Example 1. The leaching rate of platinum group metals and the impurity inhibition rate of this embodiment are tested using the same method as in Example 1. The results are shown in Table 3.

[0054] Example 9 Based on Example 1, this embodiment changes the type of polyphenolic adhesive in S1 to oxidized ammonolytic lignin. Other conditions are the same as in Example 1. The leaching rate of platinum group metals and the impurity inhibition rate of this embodiment are tested using the same method as in Example 1. The results are shown in Table 3.

[0055] Table 3

[0056] Table 3 shows that tannic acid and oxidized ammonolyzed lignin, as polyphenolic adhesives, have the best effects on promoting the leaching of platinum group metals and inhibiting impurities. This is because tannic acid contains a high density of catechol / galloyl groups (approximately 25 phenolic hydroxyl groups / molecule), while oxidized ammonolyzed lignin, through the introduction of amide groups and heterocyclic nitrogen, has a high functional group density (nitrogen content can reach 10wt%~16wt%). Both have the highest impurity inhibition rates (Al inhibition rate ≥93.5%). After introducing amino groups (-NH2) into aminated lignin, a synergistic coordination effect with phenolic hydroxyl groups is achieved, resulting in an impurity inhibition rate close to that of tannic acid, while maintaining controllable costs. Sulfonated lignin has low cost, good water solubility, and good performance, making it suitable for industrial applications. Unmodified lignin has poor performance: poor water solubility (requiring alkali dissolution), insufficient functional group density, and intermolecular π-π stacking leading to the encapsulation of active groups, significantly reducing the impurity inhibition rate.

[0057] Example 10 Based on Example 1, the amount of composite masking agent added in S4 was adjusted to 4%, and other conditions were the same as in Example 1. The leaching rate and impurity inhibition rate of platinum group metals in this example were tested using the same method as in Example 1, and the results are shown in Table 4.

[0058] Example 11 Based on Example 1, the amount of composite masking agent added in S4 was adjusted to 7%, and other conditions were the same as in Example 1. The leaching rate and impurity inhibition rate of platinum group metals in this example were tested using the same method as in Example 1, and the results are shown in Table 4.

[0059] Example 12 Based on Example 1, the amount of composite masking agent added in S4 was adjusted to 9%, and other conditions were the same as in Example 1. The leaching rate and impurity inhibition rate of platinum group metals in this example were tested using the same method as in Example 1, and the results are shown in Table 4.

[0060] Example 13 Based on Example 1, the amount of composite masking agent added in S4 was adjusted to 10%, and other conditions were the same as in Example 1. The leaching rate and impurity inhibition rate of platinum group metals in this example were tested using the same method as in Example 1, and the results are shown in Table 4.

[0061] Table 4

[0062] The results in Table 4 show that as the amount of composite masking agent increases, the leaching rate of platinum group metals and the impurity inhibition rate generally show an improving trend, but the growth rate slows down in the later stage and the performance does not improve significantly, resulting in diminishing marginal benefits.

[0063] Comparative Example 1 The difference between this comparative example and Example 1 is that the component sodium potassium tartrate was removed from Example 1, while other conditions were the same as in Example 1. The leaching rate and impurity inhibition rate of the platinum group metals in this example were tested using the same method as in Example 1, and the results are shown in Table 5.

[0064] Comparative Example 2 The difference between this comparative example and Example 1 is that the component sodium thiosulfate was removed from Example 1, while other conditions were the same as in Example 1. The leaching rate and impurity inhibition rate of the platinum group metals in this example were tested using the same method as in Example 1, and the results are shown in Table 5.

[0065] Comparative Example 3 The difference between this comparative example and Example 1 is that the component - disodium ethylenediaminetetraacetate - was removed from Example 1, while other conditions were the same as in Example 1. The leaching rate and impurity inhibition rate of the platinum group metals in this example were tested using the same method as in Example 1, and the results are shown in Table 5.

[0066] Comparative Example 4 The difference between this comparative example and Example 1 is that the component citric acid was removed from Example 1, while other conditions were the same as in Example 1. The leaching rate and impurity inhibition rate of the platinum group metals in this example were tested using the same method as in Example 1, and the results are shown in Table 5.

[0067] Comparative Example 5 The difference between this comparative example and Example 1 is that potassium sodium tartrate, sodium thiosulfate, disodium ethylenediaminetetraacetate, citric acid, and sulfonated lignin were blended instead of being treated by oxidative coupling. The leaching rate of platinum group metals and the impurity inhibition rate of this example were tested using the same method as in Example 1, and the results are shown in Table 5.

[0068] Table 5

[0069] Table 5 shows that, compared with Example 1, the deletion of any component will cause a slight decrease in the leaching rate of platinum group metals and a significant decrease in the impurity inhibition rate.

[0070] Sodium potassium tartrate is the core component for oxidative shielding; its absence results in the largest decrease in Al inhibition rate. Citric acid is a key component for surface passivation; its absence also reduces the Al inhibition rate. Sodium thiosulfate and disodium EDTA are core components for solution-phase complexation; their absence significantly reduces the inhibition rate of specific impurities (Cu / Ni or Fe / Zn). Oxidative coupling improves the impurity inhibition rate compared to simple blending. The synergistic effect of the five components on impurity inhibition is far greater than the simple sum of the individual effects of each component.

[0071] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A composite masking agent for inhibiting the co-solubility of impurities, characterized in that, The composite masking agent is a three-dimensional network complex formed by combining an oxidized cross-linked polyphenol network with a functional complexing component. The functional complexing components include sodium potassium tartrate, sodium thiosulfate, disodium ethylenediaminetetraacetate, and a surface passivating agent; the surface passivating agent is at least one selected from citric acid, phytic acid, gluconic acid, and tartaric acid. The oxidatively cross-linked polyphenol network is obtained by oxidatively cross-linking a polyphenolic adhesive, wherein the polyphenolic adhesive is selected from at least one of tannic acid, lignin, and lignin derivatives. The preparation method of the composite masking agent includes the following steps: S11. Dissolve the polyphenolic adhesive and adjust the pH to 7.0~10.0, add the oxidant, and react at 40℃~70℃ for 0.5h~6h to form an oxidative crosslinking product; S12. Dissolve potassium sodium tartrate, sodium thiosulfate, disodium ethylenediaminetetraacetate, and a surface passivating agent, and then combine them with the oxidative crosslinking compound. Adjust the pH to 4.0~5.5 to obtain a liquid composite masking agent; or spray dry the liquid composite masking agent to obtain a solid composite masking agent.

2. The composite masking agent for inhibiting impurity co-solubility according to claim 1, characterized in that, The composite masking agent comprises the following components in parts by weight: 8 to 20 parts of potassium sodium tartrate; Sodium thiosulfate 15 to 30 parts; 5 to 15 parts of disodium ethylenediaminetetraacetate; 15 to 35 parts of surface passivating agent; 5 to 20 parts of polyphenolic adhesive.

3. The composite masking agent for inhibiting impurity co-solubility according to claim 1, characterized in that, The oxidant is hydrogen peroxide, and its addition amount is 0.5% to 2.0% of the mass of the polyphenolic adhesive.

4. The composite masking agent for inhibiting impurity co-solubility according to claim 1, characterized in that, The conditions for compounding are: stirring for 30 min to 90 min at a temperature of 40℃ to 60℃.

5. The composite masking agent for inhibiting impurity co-solubility according to claim 1, characterized in that, The lignin derivative is sulfonated lignin, carboxymethylated lignin, aminated lignin, or oxidized ammonolytic lignin.

6. The application of the composite masking agent for inhibiting impurity co-solubility as described in any one of claims 1 to 5 in the leaching of platinum group metals from spent catalysts, characterized in that, The composite masking agent is used to suppress the co-dissolution of base metal impurities during the leaching of platinum group metals from the spent catalyst. The base metal impurities include at least one of aluminum, iron, nickel, copper, and zinc. The composite masking agent is added to the spent catalyst after decarbonization pretreatment, the pH is adjusted to 4.0-5.5, the catalyst is stirred for pretreatment, and a hydrochloric acid-sulfuric acid mixture is added to reduce the pH of the system to 2-3.

7. The application according to claim 6, characterized in that, A composite masking agent is added to the spent catalyst after decarbonization pretreatment, and the catalyst is treated for 30 to 90 minutes at a pH of 4.0 to 5.5 and a temperature of 50°C to 70°C. This allows the composite masking agent to form a three-dimensional network structure in situ on the surface of the spent catalyst support before acidic oxidation leaching of platinum group metals is carried out.

8. The application according to claim 6 or 7, characterized in that, The amount of the composite masking agent added is 4% to 10% of the dry mass of the spent catalyst.

9. The application according to claim 8, characterized in that, The specific methods of the application include: Decarbonization pretreatment of spent catalysts; The decarbonized pretreated waste catalyst is added to the reactor, water or dilute hydrochloric acid is added to adjust the slurry, and the liquid-solid ratio is controlled at 3~5:1; then a composite masking agent is added, the pH is adjusted to 4.0~5.5, the temperature is 50℃~70℃, and the pretreatment is stirred for 30min~90min. Add hydrochloric acid-sulfuric acid mixture to lower the pH of the system to 2-3, slowly add sodium chlorate as oxidant, and raise the temperature to 85℃-105℃; continue stirring for 2-4 hours to allow the platinum group metals to enter the solution in the form of chloride complexes; after leaching is completed, filter under pressure to obtain a leachate with low impurity content.

Citation Information

Patent Citations

  • Microcapsule wall material composition used for odor masking and preparation method and application thereof

    CN109846853A

  • Joint inspection grading method for amino acid nitrogen and salt of soy sauce

    CN120427607A